Root canal treatment with calcium hydroxide. II. Effect of instrumentation beyond the apices - Holland, R.; Nery, M. J.; de Mello, W.; de Souza, V.; Bernabé, P. F.E.; Filho, J.A.Otoboni (Elsevier, 1979)
Root canals of dog premolar teeth were instrumented beyond the apices and enlarged up to the size of a No. 40 or 80 file and filled with calcium hydroxide up to the foramen. Ninety days later the histologic data showed more favorable results with the root canals instrumented until file No. 80. © 1979.